Lipid Antioxidant and Galactolipid Remodeling under Temperature Stress in Tomato Plants - Spicher, Livia; Glauser, Gaetan; Kessler, Felix (Frontiers in Plant Science, 2016)
Increased temperatures are a major scenario in climate change and present a threat to plant growth and agriculture. Plant growth depends on photosynthesis. To function optimally the photosynthetic machinery at the thylakoid membrane in chloroplasts continuously adapts to changing conditions. Here, we set out to discover the most important changes arising at the lipid level under high temperature (38°C) in comparison to mild (20°C) and moderately cold temperature (10°C) using a non-targeted lipidomics approach. To our knowledge, no comparable experiment at the level of the whole membrane system has been documented. Here, 791 molecular species were detected by mass spectrometry and ranged from membrane lipids, prenylquinones (tocopherols, phylloquinone, plastoquinone, plastochromanol), carotenoids (β-carotene, xanthophylls) to numerous unidentified compounds. At high temperatures, the most striking changes were observed for the prenylquinones (α-tocopherol and plastoquinone/-ol) and the degree of saturation of fatty acids in galactolipids and phosphatidyl ethanolamine. Photosynthetic efficiency at high temperature was not affected but at moderately cold temperature mild photoinhibition occurred. The results indicate that the thylakoid membrane is remodeled with regard to fatty acid saturation in galactolipids and lipid antioxidant concentrations under high temperature stress. The data strongly suggest that massively increased concentrations of α-tocopherol and plastoquinone are important for protection against high temperature stress and proper function of the photosynthetic apparatus.